The floating mire of Voulkaria lake (Prefecture of Aitoloakarnania - ΜΠΟΥΖΙΝΟΣ Α.; ΠΑΠΑΖΗΣΙΜΟΥ Σ.; ΧΡΗΣΤΑΝΗΣ Κ.; ΤΖΕΔΑΚΗΣ Π. Κ. (Bulletin of the Geological Society of Greece, 2001)
The 940-ha-large Voulkaria lake is located in a Quaternary graben at the northwestern edge of Aitoloakarnania province, Western Greece. It is a shallow lake with a maximum depth of 2.5 m. A small fen forms at the southern shore of the lake. Neogene sediments (marls, sandstones and conglomerates) and alluvial deposits form the northwestern and southeastern parts of the graben, while red soils (terra rossa) cover the northern part. Helophytes thrive along the shore of the lake. The dominant species are Phragmites australis, Scirpus lacustris, Cladium mariscus, Typha spp., Salix spp. Helophytic vegetation also grows on a floating mat which consists of aquatic plants and roots of some helophytes. Peat displays a homogenous matrix. The degree of humification after von Post ranges between 7-8. The peat contains mainly fine roots, epidermic fragments of Phragmites australis, fruits and seeds from Cladium mariscus, Carex spp. and woody tissues of Salix spp. Moisture and ash contents lie between 56-82% and 37-63%, respectively. Palynomorphs of upland and helophytic vegetation were recognized in the sediments. Radiocarbon dating suggests that peat accumulation started some 1450 years ago. The floating mire of Voulkaria lake is one of the most important wetlands of Amvrakikos Gulf. It consists a unique ecosystem in our country, the conservation of which should be of high priority because of its ecological value.